Behavioral taxation: Opportunities and challenges - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
The field of behavioral taxation dates back at least to the 1950s. In this contribution I will explore the opportunities and challenges in the area, with a particular focus on tax compliance. I will focus on the data required to make further progress, discussing what can be improved when working with surveys and how the field could benefit from open government data initiatives. I focus on collaborative efforts among scientists as well as with the government or the tax administration and examine many potential areas of exploration. The opportunities currently emerging due to digitalization provide not only interesting avenues for collaborations but also a natural method of using tools such as lab and field experiments. In addition, I will discuss potential dangers faced by the field of behavioral economics that also threaten the field of behavioral taxation.
Keywords: 330; Steuerpolitik; Verhaltensökonomik; Steuermoral; Datenerhebung; Experiment; Digitalisierung